PROJECT-BASED LEARNING IN TEACHING WRITING: THE IMPLEMENTATION AND STUDENTS’ OPINION - Ningtyas Orilina Argawati; Lilis Suryani (University of Kuningan, 2020)
Writing becomes the most challenging skill for the students as it needs more time to develop and tend to raise problem to students. Therefore, project based learning is offered to solve the problems in writing. Some experts believe that project based learning (PBL) can provoke the students to get new knowledge through their own project. This research reports on the implementation of project based learning in teaching writing. The objectives of the research are to know the implementation of project based learning in elevating the students’ ability on writing and to know the students’ opinion of the implementation of project based learning in teaching writing. Qualitative was used as a research method and classroom action research as a research design. The participants of the research were fourth semester students in one university in Cimahi, West Java. The collected data were obtained through observation, writing test and interview. Then, data were analysed based on triangulation. As result, it was found that the implementation of project based learning in teaching writing worked well. It could be seen from the students’ responses during the implementation of this method as they gave positive opinion toward the method used; they actively involved in learning process. PBL was proved on helping the students wrote well. Besides, the project given engaged the students in solving a real problem and answering it. In other word, this project could develop the students’ critical thinking and it could be a meaningful project for them.